Synthetic Aperture Imaging of Antenna Array Coded - Yanfei WANG; Heping LI; Song HAN (Leida xuebao, 2023)
The theoretical azimuth resolution of Synthetic Aperture Radar (SAR) is half the antenna length, presenting conflicting requirements on the antenna for SAR high-resolution and long-distance imaging. In this paper, a method for antenna array coding synthetic aperture imaging is proposed. By dividing long antennas into subarrays to work together, the space energy utilization rate can be improved, a high resolution of the small antennas of the subarrays and a high gain of the long antennas of the whole array are achieved, and the problem that it is difficult to balance high-resolution and far-distance imaging is solved. On the basis of introducing the basic concept of array coding, the imaging model and processing flow of array coding radar are given, and the system performance metrics, such as resolution, signal-to-noise ratio, Pulse Repetition Frequency (PRF), and range-azimuth ambiguity, are theoretically analyzed and discussed. In a flight test experiment, a 0.5 m antenna is divided into four sub-arrays, and a strip-map image with a resolution of 0.1 m and a swath width of 8 km is obtained, which breaks the restriction of small-area imaging when traditional SAR adopts the spotlight mode to achieve high resolution. This new method effectively solves the limitations of traditional SAR and extends the signal dimension, providing a technical basis for enhancing radar system capability. Theoretical analysis and experimental results verify the considerable advantages and engineering implementation feasibility of the proposed method.